Democracy, organized interests, and rice policy in Thailand - Thanapan Laiprakobsup (Journal of Current Science and Technology, 2013)
This paper examines the factors affecting the Thai government’s decision to increase (or reduce) policy controls on rice. It is proposed that authoritarian governments are more likely to impose more control programs on rice, whereas democratic governments are more likely to reduce such controls on the sector. Also, when the agricultural industry coalesces, and when farmers are united, the government reduces controls on the sector. In studying rice policy in Thailand and using multiple regression models for the analysis, the author finds democratic regimes to be likely to reduce control programs in the rice sector. In addition, the Thai government is likely to reduce such controls on the rice sector when rice businesses are highly coordinated. On the other hand, the unity of rice growers does not have a significant impact on the government’s degree of intervention. The results indicate a difference in the ability to influence policy. The industry has an influence on the government’s policy. In contrast, agricultural farmers struggle to participate in the Thai government’s policymaking.